Novel 2,5-disubstituted-1,3,4-oxadiazole derivatives as MAO-B inhibitors: Synthesis, biological evaluation and molecular modeling studies - KAYMAKÇIOĞLU, BEDİA; TOK, FATİH (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2021)
Thirty novel 2,5-disubstituted-1,3,4-oxadiazole derivatives bearing urea moiety were designed and synthesized. IR, 1H-NMR, 13C-NMR and mass spectroscopic methods and elemental analysis were used to confirm the structures of the compounds. Their monoamine oxidase inhibitory activity was determined against the MAO-A and MAO-B isoforms. None of the compounds showed the potent MAO-A inhibitory activity, while the MAO-B inhibition was significantly found in the range of 62 to 98%. Among them, the compounds H8, H9 and H12 bearing chloro substituent at the fourth position of phenylurea were found to show potent monoamine oxidase B inhibitory activity with IC50 values 0.039-0.066 mu M. To define and evaluate the interaction mechanism between compound H8 and monoamine oxidase B, molecular docking studies have been made.
Keywords: MAO inhibitors; 1; 3; 4-oxadiazole; Molecular docking; Urea derivatives; IN-SILICO EVALUATION; DESIGN; VITRO; 1,3,4-OXADIAZOLE; COMPLEXES; HYDRAZONE; DOCKING; MOIETY